Consumer willingness to pay a premium for a functional food in Ghana - Badu-Gyan , Farida; Owusu, Victor (Applied Studies in Agribusiness and Commerce, 2017)
Interest in functional foods has been growing in sub-Saharan Africa due to consumer concerns with diet and nutrition. This paper analyses consumer awareness, perceptions and effects of the determinants of consumer willingness to pay (WTP) a premium for Moringa bread in Ghana. An ordered probit model is employed. The empirical results indicate that consumer knowledge of the nutritional and health benefits of Moringa bread is what matters most to consumers in respect of their WTP a higher premium for the product. Consumers with knowledge on Moringa products are more willing to pay above 50% price premiums for Moringa bread. Fruitful policy recommendations are made in the paper.JEL code: D12